Association of sweetened beverage intake with incident risk of breast cancer: a prospective cohort study - Huang, Jiayi; Wu, Fuhua; Chen, Weiwei; Ye, Ding; Tian, Yiping; Li, Jiayu; Guo, Jing; Wang, Jianming; Mao, Yingying; Sun, Xiaohui (Frontiers in Nutrition, 2026)
BackgroundThis large prospective cohort study aimed to clarify uncertain associations between sugar-sweetened beverages (SSB), artificially sweetened beverages (ASB), pure fruit/vegetable juice and breast cancer risk.MethodsIn 86,247 cancer-free UK Biobank participants at baseline, Cox proportional hazard models were performed to investigate the associations of SSB, ASB, pure fruit/vegetable juice with incident breast cancer risk.ResultsIn total, 2,644 cases of incident breast cancer occurred during the median follow-up of 10 years. In Cox proportional hazards model, participants consuming >0 and ≤1 serving/day of pure fruit/vegetable juice had a hazard ratio (HR) of 1.13 (95% CI: 1.05–1.23; P = 0.002) compared to non-consumers (P = 0.004 for trend). However, no associations were observed for SSB and ASB with breast cancer risk. We also found that replacing 1 serving per day of pure fruit/vegetable juice with ASB was associated with 10% lower risk of incident breast cancer in substitution analyses.ConclusionsOur findings indicated that pure fruit/vegetable juice was associated with increased risk of breast cancer, highlighting the potential role of sweetened beverages in breast cancer prevention strategies and call for further research to understand the underlying mechanisms.